Goal and Personality Trait Development in Emerging Adulthood. (article). - Roberts, Brent, W.
The present research examined continuity and change in the importance of major life and the relation between change in goals and change in personality traits over the course of college. Participants rated the importance of their life goals 6 times over a 4-year period and completed a measure of the Big Five personality traits at the beginning and end of college. Like personality traits, life goals demonstrated high levels of rank -order stability. Unlike personality trait assessed during the same period and in the same sample, the most importance of life goals decreased over time. Moreover, each goal domain was marked by significant individual differences in change, and these individual differences were related to changes in personality traits. These findings provide insights into the relatively unstudied question of how life goals change during emerging adulthood. -- (from the author)